Mental and Physical Capability as the Requirement for Indonesian Presidential Candidate: Legal Ratio and the Development of Regulation - Susi Dwi Harijanti; Mei Susanto; Firman Manan; Muhammad Yoppy Adhihermawan; Ilham Fajar Septian (Jurnal Ilmiah Kebijakan Hukum, 2022)
The Third Amendment to the 1945 Constitution has regulated new requirements for presidential candidates. One of which is the requirement to be mentally and physically capable of carrying  out the duties and obligations of the presidential office. This research aims to find the reason for formulating norms or legal ratio of the formation of such a requirement. The nature of this research is qualitative research using a normative-empirical and comparative approach. The results reveal several legal ratios of the requirement. First, the requirement is considered important because the president has the highest position within the governmental structures. Second reason refers to the close relation between health and decision-making matters, and the third demonstrates reasonable and justifiable limitations from the perspective of human rights. Comparison with several countries exposes that the requirement is fundamental since the president has dual functions, namely a head of state and a chief of government. This research also exhibits that the legal basis of the requirement is not in accordance with the 1945 Constitution since the existing regulation takes the form of the Decree of the General Election Commission. Therefore, this research recommends the appropriate legal basis to further regulate mental and physical requirements by law which regulates some fundamental principles dealing with such requirements.